Determinan Perilaku Merokok Pada Sopir Lintas Barat Di Satuan Pelayanan Terminal Tipe A Kota Banda Aceh Tahun 2022 - Rizki Mulyana; Ibrahim Laweung; Anwar Arbi (Journal of Health and Medical Science, 2023)
Smoking behavior can cause disease that can lead to death. Tobacco consumption is one of the health challenges in Indonesia, where the number of adult males who smoke is 62.9%. Aceh Province is ranked 13th with a smoking percentage reaching 28.30%, this figure is high which is close to the national smoking rate of 28.96%. This study aims to determine the determinants of smoking behavior in western cross-country drivers at the Type A Terminal Service Unit in Banda Aceh City in 2022. This research is descriptive analytic with cross sectional design. The population in this study were all western transboundary drivers who were in the Type A Terminal Service Unit of Banda Aceh City, totaling 294 drivers. Sampling of 76 drivers using proportional random sampling technique. Data collection was carried out from 1-5 March 2022 using a questionnaire through interviews. Data were analyzed univariately and bivariately using the chi square test with the Stata computer program. Univariate analysis showed that 51.32% of drivers with heavy smoking behavior, 53.95% of drivers who have good knowledge, 56.58% of drivers who influence cigarette advertisements, 68.42% of drivers whose social environment is supportive, 64.47% of drivers who experience stress. Bivariate analysis showed that there was a relationship between cigarette advertising (p value 0.042) and stress levels (p value 0.003), whereas knowledge (p value 0.566) and social environment (p value 0.102) had no relationship with smoking behavior among drivers.